P-Rex2 suppresses glucose uptake into liver and skeletal muscle through different adaptor functions - Elpida Tsonou; Julia Y. Chu; Polly A. Machin; Anna G. Roberts; Anne Segonds-Pichon; David Baker; David C. Hornigold; Heidi C. E. Welch (Scientific Reports)
Abstract P-Rex2 is a Rac guanine-nucleotide factor (Rac-GEF) that controls glucose homeostasis. This role is thought to be mediated through its adaptor function inhibiting Pten rather than through its Rac-GEF activity, but this remains to be demonstrated. To examine this question, we have investigated the roles of P-Rex2 in glucose homeostasis using Prex2 –/– and catalytically-inactive Prex2 GD mice. We show that P-Rex2 is required for insulin sensitivity but limits glucose clearance, suppressing glucose uptake into liver and skeletal muscle independently of its catalytic activity. In hepatocytes, P-Rex2 suppresses Glut2 cell surface levels, mitochondrial membrane potential and mitochondrial ATP production. We identify the orphan GPCR Gpr21 as a P-Rex2 target and propose that P-Rex2 limits hepatic glucose clearance by controlling Gpr21 trafficking. In skeletal muscle cells, P-Rex2 suppresses glucose uptake through a separate adaptor function, independently of Gpr21. Additionally, P-Rex2 suppresses insulin secretion by pancreatic islets and plasma insulin levels. Finally, P-Rex2 plays distinct Rac-GEF activity dependent and independent roles in PIP3 production in liver and skeletal muscle, respectively. Together, our study identifies complex roles of P-Rex2 in glucose homeostasis, mediated through largely GEF-activity independent mechanisms which include the GPCR Gpr21 in hepatocytes and but are not obviously linked to the regulation of Pten.